Social history of the Jews in antiquity: studies in dialogue with Albert Baumgarten - Bar Asher Sigal, Mikhal; Ben-Dov, Yonatan (Texts and studies in ancient Judaism, 2021)
Der vorliegende Band versammelt Beiträge renommierter internationaler Wissenschaftler, die im akademischen Dialog mit dem Werk von Albert Baumgarten stehen. Sie kontextualisieren antike jüdische Texte, um die Antike im Allgemeinen zu beleuchten und befassen sich mit Texten aus der klassischen Altertumswissenschaft, des hellenistischen Judentums, der Sekten zur Zeit des Zweiten Tempels, der rabbinischen Literatur und verschiedener Facetten des frühen Christentums. Darüber hinaus beschäftigen sich einige Artikel mit vergleichender Religionswissenschaft, Wissenssoziologie, Anthropologie und Wirtschaftsgeschichte. Zusammengenommen bilden die Artikel in diesem Band eine eingehende Analyse der Sozialgeschichte der Juden in der Antike.InhaltsübersichtMichal Bar-Asher Siegal/ Jonathan Ben-Dov/Eyal Regev: Introduction I. Second Temple Studies Gabriele Boccaccini: Jewish Scholarship on the Second Temple Period: From the Renaissance to Albert I. Baumgarten − Martin Goodman: Philo's Extreme Allegorists Revisited −Maxine Grossman: The Dead Sea Sectarians: Breaking the Boundaries of an Essene-Shaped Space − Charlotte Hempel: Self-Fashioning in the Dead Sea Scrolls: Thickening the Description of What Rule Texts Do − Sylvie Honigman: Social and Economic Upheavals and the »De-Traditionalization« of Judean Society in Hellenistic Times: The Background to Sectarianism − Steve Mason: John of Gischala and Simon bar Giora from Gerasa: A National Revolt? − Eyal Regev: The Practice of Piety: The Puritans and Qumran − Daniel Schwartz: Who Brought on Antiochus's Decrees? On the Chaotic and »Worthless« Prehistory of Bickerman's Gott der Makkabäer − Daniel Stökl Ben Ezra: The Place of 4QMMT in the Corpus of Qumran Manuscripts: Beyond the Sussmann-Schiffman Dichotomy II. Rabbinics and Early Christianity Michal Bar-Asher Siegal: Public Confession in the Babylonian Talmud and in Contemporary Christian Sources − Jonathan Ben-Dov: Rabbi Yehuda Hanasi and the Roman Year − Shaye J.D. Cohen: Are Women and Gentiles »Persons« (Adam, Benei Adam) in the Eyes of the Mishnah? − Steven Fraade: »Reading Leads to Translating« in a Multilingual Context: The View from Early Rabbinic Texts (and Beyond) − Maren Niehoff: Celsus's Jew in Third-Century Caesarea: Tracing Hellenistic Judaism in Origen's Contra Celsum − Adele Reinhartz: The Fourth Gospel and the First-Century Outreach Campaign to the Gentiles − Adiel Schremer: How Can Rabbinic Narratives Talk History? III. Sociological Models and Ancient Judaism: Former Students in Dialogue Stéphanie E. Binder: Contre Apion I. 183–205; II. 43. Quelle audience pour les passages attribués à Hécatée? −Shlomit Kendi Harel: Yom Hakippurim: Day, Year, or Eschatological Jubilee? − Hillel Newman: Religious Conviction (Religion) and Ethical Practice (Morality) in a Jewish Group in Antiquity: Strengthening a Sociological Approach − Samuele Rocca: The Jews among the Middle Ruling Class of Roman Italy? An Elaboration of a Thesis by Paul Veyne − Elisheva, Shoshana, Margalit, and Naama Baumgarten: Remembering it Well: In Lieu of a Retrospective